2021
DOI: 10.1371/journal.pone.0251956
|View full text |Cite
|
Sign up to set email alerts
|

Potential antigenic targets used in immunological tests for diagnosis of tegumentary leishmaniasis: A systematic review

Abstract: Immunological tests may represent valuable tools for the diagnosis of human tegumentary leishmaniasis (TL) due to their simple execution, less invasive nature and potential use as a point-of-care test. Indeed, several antigenic targets have been used with the aim of improving the restricted scenario for TL-diagnosis. We performed a worldwide systematic review to identify antigenic targets that have been evaluated for the main clinical forms of TL, such as cutaneous (CL) and mucosal (ML) leishmaniasis. Included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…In contrast, a systematic review by Zanetti et al revealed that more specific (recombinant) antigens yielded better diagnosis results, that is, sensitivity (93.8–100%) and specificity (82.5–100%) for ATL, compared with crude soluble antigen-based ELISAs [ 27 ]. More than 70 different antigens have been evaluated as ELISA diagnostic markers for (M)CL [ 28 ]. For example, an ELISA based on a recombinant conserved Leishmania hypothetical protein (which showed a high amino acid sequence homology between CL- as well as VL-causing Leishmania species) was found to be more specific and sensitive in detecting (M)CL patients than an ELISA based on L. braziliensis soluble antigens [ 29 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…In contrast, a systematic review by Zanetti et al revealed that more specific (recombinant) antigens yielded better diagnosis results, that is, sensitivity (93.8–100%) and specificity (82.5–100%) for ATL, compared with crude soluble antigen-based ELISAs [ 27 ]. More than 70 different antigens have been evaluated as ELISA diagnostic markers for (M)CL [ 28 ]. For example, an ELISA based on a recombinant conserved Leishmania hypothetical protein (which showed a high amino acid sequence homology between CL- as well as VL-causing Leishmania species) was found to be more specific and sensitive in detecting (M)CL patients than an ELISA based on L. braziliensis soluble antigens [ 29 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…ELISA, because of its high sensitivity and specificity, remains a major method, although the choice of antigen can influence sensitivity, requiring well-equipped facilities. The immunochromatographic test (ICT) using the rK39 antigen constitutes a rapid, economical, and non-invasive screening test for visceral leishmaniasis, remaining effective for large-scale screening despite variations in performance between epidemiological populations [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, recent guidance from the WHO Diagnostic Technical Advisory Group for neglected tropical diseases (NTDs) highlights the need to develop new point-of-care tests for Cutaneous Leishmaniasis (CL). The currently available CL Detect Rapid Test fails to meet the requisite diagnostic performance standards of reaching 95% sensitivity for point-of-care waiting for the next generation of CL-RDT based on antigen detection that should differentiate between L.tropica, L.major, and other species [1,29,30].…”
Section: Discussionmentioning
confidence: 99%